2008
DOI: 10.1016/j.jcrs.2007.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prophylactic nonsteroidal antiinflammatory drugs on cystoid macular edema assessed using optical coherence tomography quantification of total macular volume after cataract surgery

Abstract: Used prophylactically after cataract surgery, ketorolac 0.5% was efficacious in decreasing postoperative macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 23 publications
0
55
0
3
Order By: Relevance
“…The Almeida, Donnenfeld, and Wittpenn studies were determined to have a statistical power of 2.5%, 45.1%, and 53.1%, respectively. 9,10,12 The power of the Chatiziralli study 11 was inestimable because of the fact that there were no incidents of CME in either group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Almeida, Donnenfeld, and Wittpenn studies were determined to have a statistical power of 2.5%, 45.1%, and 53.1%, respectively. 9,10,12 The power of the Chatiziralli study 11 was inestimable because of the fact that there were no incidents of CME in either group.…”
Section: Discussionmentioning
confidence: 99%
“…Two RCTs used ketorolac tromethamine 0.4% whereas the other two employed ketorolac tromethamine 0.5% Two RCTs utilized placebo drops as their control group compared with the other two RCTs using only a steroid and antibiotic Variation in sample size Differences in time when ketorolac was administered (pre-, peri-, and/or postoperatively) Only one RCT analyzed contrast sensitivity 9 Two RCTs assessed CME via OCT 9,12 All but Almeida et al 12 evaluated best-corrected visual acuity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective studies evaluated the effect of a postoperative NSAID on the development of macular oedema after phacoemulsification. 7,[17][18][19] At 5 weeks after phacoemulsification, Miyake's study documented 5.7 vs 54.7% angiographic CME in the eyes that received only diclofenac 0.1% vs the eyes that received only flurometholone 0.1%, respectively. 7 Two recent studies confirmed these findings when an NSAID was used preoperatively and postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…58 However, it was not until much later that ketorolac 0.5% and diclofenac 0.1% proved effective in treating this condition. Ketorolac 0.5% was efficacious in decreasing post-operative macular oedema when used prophylactically after cataract surgery, 59 while diclofenac 0.1% was more effective than betamethasone in preventing angiographic CME and blood-aqueous barrier disruption after small-incision cataract surgery. 60 While no randomised trials have yet been conducted to test the ability of the two new-generation topical NSAIDs -nepafenac and bromfenac -in treating CME, numerous reports suggest that these agents also have activity against this condition.…”
Section: Cystoid Macular Oedemamentioning
confidence: 94%